2017
DOI: 10.1111/joic.12380
|View full text |Cite
|
Sign up to set email alerts
|

Role of deferred stenting in patients with ST elevation myocardial infarction treated with primary percutaneous coronary intervention: A systematic review and meta‐analysis

Abstract: A deferred stenting strategy could be a feasible alternative to the conventional approach with immediate stenting in "selected" STEMI patients undergoing pPCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
0
16
0
6
Order By: Relevance
“…These findings were supported by a meta‐analysis of six randomized studies with 1126 patients which found decreased mortality (RR:2.55, 95%CI:1.42‐4.58, P < 0.01) at 13 month follow up in patients with multivessel disease who had staged revascularization of non‐culprit lesions as opposed to CR at the time of index procedure . However, other meta‐analyses found CR, regardless of timing as index or staged procedure, was associated with a lower risk of MACCE compared to culprit only intervention driven by lower risk of revascularization without any difference in mortality . Therefore, more randomized trials are required to investigate the impact of CR on all‐cause mortality in this population.…”
Section: Primary Pci For Stemimentioning
confidence: 81%
See 1 more Smart Citation
“…These findings were supported by a meta‐analysis of six randomized studies with 1126 patients which found decreased mortality (RR:2.55, 95%CI:1.42‐4.58, P < 0.01) at 13 month follow up in patients with multivessel disease who had staged revascularization of non‐culprit lesions as opposed to CR at the time of index procedure . However, other meta‐analyses found CR, regardless of timing as index or staged procedure, was associated with a lower risk of MACCE compared to culprit only intervention driven by lower risk of revascularization without any difference in mortality . Therefore, more randomized trials are required to investigate the impact of CR on all‐cause mortality in this population.…”
Section: Primary Pci For Stemimentioning
confidence: 81%
“…62 64 However, other meta-analyses found CR, regardless of timing as index or staged procedure, was associated with a lower risk of MACCE compared to culprit only intervention driven by lower risk of revascularization without any difference in mortality. 65,66 Therefore, more randomized trials are required to investigate the impact of CR on all-cause mortality in this population.…”
Section: Trials Of Complete Revascularizationmentioning
confidence: 99%
“…Еще одним вариантом кардиопротекции является ишемическое коронарное посткондиционирование, суть которого заключается в проведении серии циклических раздуваний баллона в просвете КА непосредственно после имплантации стента и восстановления [28] • Минимально инвазивная стратегия у избранных пациентов (П М) [32,33] • Ишемическое посткондиционирование (П М К) [34,35] • Механическая тромбэктомия (П М) [2] • Эксенатид, лираглутид (П) [36] • Оксид азота (П) [37] • Блокаторы кальциевых каналов (П М) [38] • Предсердный натрийуретический пептид (П) [36] • Гипотермия (П) [28] • Аденозин (П М) [39] • Прерывистая окклюзия коронарного синуса (П) [40] • Эксенатид, лираглутид (П) [36] • Предсердный натрийуретический пептид (П) [36] • Гипотермия (П) [28] • Аденозин (П М) [39] • Цилостазол (П) [42] Не рекомендовано…”
Section: анализ профилактических и лечебных тактикunclassified
“…• Дистанционное ишемическое кондиционирование (П М K) [29,30] • Блокаторы гликопротеиновых IIb/IIIa рецепторов тромбоцитов (К) [1] • Тикагрелор (К) [7] • ITF-1697, блокаторы циклооксигеназы (К) [7] • Дистанционное ишемическое кондиционирование (П М K) [29,30] • Рутинная мануальная аспирационная тромбэктомия (П М К) [41] • Рутинное применение блокаторов гликопротеиновых IIb/IIIa рецепторов тромбоцитов (П М К) [1] • Рутинное отсроченное стентирование (П М К) [33] • Интракоронарное введение фибринолитика (П) [15] • Циклоспорин А (П К) [36] • MTP-131 (П) [36] • TRO40303 (П) [36] • Ингибиторы протеинкиназы C-дельта (П) [36] • Устройства для профилактики дистальной эмболизации (П К) [2] • Оксигенация (П К) [1] • Никорандил (П М) [2] • Пекселизумаб (К) [2] • FX06 (П) [2] • Эритропоэтин (П) [2] • Эпинефрин (П) [2] • Внутриаортальная баллонная контрпульсация (П) [8] • Стволовые клетки (П М) [43] Примечание. П -проведены небольшие пилотные клинические исследования; М -выполнен метаанализ; К -проведено крупное рандомизированное клиническое исследование с оценкой твердых конечных точек; К Ппродолжается крупное клиническое исследование; Э -согласованное мнение экспертов коронарного кровотока.…”
Section: анализ профилактических и лечебных тактикunclassified
“…All patients should proceed urgently to the catheterization laboratory, and flow may need to be restored with a wire or gentle predilatation with a balloon. If high burden of thrombus is seen, deferred stenting with an interim period of adjunctive antiplatelet/anti thrombotic therapy may be useful to reduce the thrombus load and minimize complications (such as no-reflow) at time of stenting [47,48].…”
Section: Deferred Stentingmentioning
confidence: 99%